Diabetes in childhood and adolescence - Chiarelli, Francesco; Dahl-Jorgensen, Knut; Kiess, Wieland 1958- (Pediatric and adolescent medicine, 2005)
Diabetes mellitus is one of the most frequent chronic diseases affecting children and adolescents. The number of young children being diagnosed with type 1 diabetes is increasing worldwide and an epidemic of type 2 diabetes already at a young age is being observed in most societies around the world.In this book, leading experts from the USA, Europe and Israel provide a state-of-the-art summary of today’s knowledge in the field of pediatric and adolescent diabetes. A number of excellent chapters deliver insight into the basic understanding of which factors contribute to or prevent the development of diabetes in young people. Other contributions provide tools for the clinician to manage the care of the child and adolescent with diabetes. In addition, knowledge from the latest scientific studies on the molecular biology of diabetes is also presented.Providing a summary of the most recent scientific discoveries related to pediatric and adolescent diabetes, this volume will be of special interest to pediatricians, endocrinologists and health care specialists who work with children suffering from the disease